Agency, Firm Growth, and Managerial Turnover - ANDERSON, RONALD W.; BUSTAMANTE, M. CECILIA; GUIBAUD, STÉPHANE; ZERVOS, MIHAIL (Journal of Finance, 2018)
ABSTRACT We study managerial incentive provision under moral hazard when growth opportunities arrive stochastically and pursuing them requires a change in management. A trade‐off arises between the benefit of always having the “right” manager and the cost of incentive provision. The prospect of growth‐induced turnover limits the firm's ability to rely on deferred pay, resulting in more front‐loaded compensation. The optimal contract may insulate managers from the risk of growth‐induced dismissal after periods of good performance. The evidence for the United States broadly supports the model's predictions: Firms with better growth prospects experience higher CEO turnover and use more front‐loaded compensation.